Modeling of hydraulic and energy efficiency indicators for water supply systems - Nogueira Vilanova, Mateus Ricardo [UNESP]; Perrella Balestieri, Jose Antonio [UNESP] (Elsevier B.V., 2015)
The present work approaches the necessity of the hydraulic and energetic efficiency indicator development for the management and decision making of water supply systems (WSSs) that can enable the comparison between the current situation of the system with its optimal technical condition regarding the energy and hydraulic terms. Such indicators must consider and represent the physical and operational components which integrate the hydraulic and energetic conversion processes in WSSs. The optimal technical condition refers to the target-value of the analyzed variable, which makes possible the lowest consumption/demand of electricity and hydraulic head, or their better use, simultaneously meeting the operational requirements of the system. The literature registers the lack of efficiency indicators for the analysis of WSSs, since the existing indicators only address the energy situation of these systems, which are not related with the energy efficiency and conservation potentials. The evaluation of the global energy efficiency of WSSs depends on the individual and separated analysis of the various physical components and energy conversion processes. In order to sustain the decision making, such individual analysis needs to be associated with the hydraulic and energy efficiency measures applicable to the system. Three technological hydraulic and energy efficiency indicators for water supply systems (WSSs) are proposed: hydraulic energy recovery indicator; optimized pumping operation indicator; and supplied hydraulic head indicator. These indicators consider the existing energy and hydraulic flows of the WSSs, allowing the full assessment of the possibilities for the energy efficiency improvements of the WSSs arising from different physical and operational energy efficiency measures. The proposed indicators are tested in real cases that show their application and potentiality. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Energy efficiency measurement; Decision making; Hydraulic and energy optimization